2014
DOI: 10.1186/1471-2458-14-581
|View full text |Cite
|
Sign up to set email alerts
|

‘This diarrhoea is not a disease …’ local illness concepts and their effects on mothers’ health seeking behaviour: a qualitative study, Shuhair, Yemen

Abstract: BackgroundGlobally, about seven million children under the age of five died in 2011. Local illness concepts are thought to be related to inappropriate health-seeking behaviour, and therefore, lead to child mortality. The aim of this study was to contribute to the definition of common local illness concepts with their effects on health-seeking behaviour for common childhood illnesses.MethodsA qualitative focus group study was conducted between April 1 and 6, 2013. Participants were drawn purposefully from the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Many studies have found that biomedical drugs, and particularly injections, are perceived as the most powerful form of medicine [13, 30, 31]. However, this study adds nuance to these findings, indicating that it does not necessarily follow that they are most appropriate, while herbal medicines also had gradients of power and appropriateness.…”
Section: Discussionmentioning
confidence: 66%
“…Many studies have found that biomedical drugs, and particularly injections, are perceived as the most powerful form of medicine [13, 30, 31]. However, this study adds nuance to these findings, indicating that it does not necessarily follow that they are most appropriate, while herbal medicines also had gradients of power and appropriateness.…”
Section: Discussionmentioning
confidence: 66%
“…Not only was the use of formal healthcare for illness with a cough low, but this decreased over time. Children's cough symptoms can be easily overlooked unless production of thick sputum or persistent over a long time ( 20 , 21 ). Such misconceptions can put children at risk because mothers often think that formal treatment is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the FHC is to help families recognize danger signs and improve their treatment-seeking behavior in accordance with evidences that show correlation between treatment seeking and neonatal mortality. [11][12][13] In addition to recognition of danger signs, local interpretation of illnesses, 14,15 knowledge of causes, perception of severity of illnesses, and the helpfulness of treatment also affect treatment-seeking behavior. 15−19 Better information about the social processes, the timing and type of care-seeking actions, and treatments received before death are critical to identifying modifiable factors to prevent avoidable deaths.…”
Section: Introductionmentioning
confidence: 99%